Untitled excerpts. - nadjaVilenne, Liège (Maastricht : Jan van Eyck Academie, 2005)
Andrade Tudela, Armando ; Andreasen, Kasper ; Buth, Peggy ; Hagenbeek, Natascha ; Garrison, Geoffrey ; Kakhidze, Alevtina ; Kirsch, Johanna ; Seibold, Stefanie ; Traoré, Saliou
Untitled excerpts, nadjaVilenne, Liège, 16 December 2005 - 9 January 2006
boek